Digital Flipbook Media Improves Writing Skills in Primary Schools: Media Buku Elektronik Interaktif Meningkatkan Keterampilan Menulis di Sekolah Dasar - Fitriya, Lailil; ZULIKHATIN NUROH, ERMAWATI (Indonesian Journal of Education Methods Development, 2025)
General background: Writing skill is a fundamental literacy competence that supports students’ ability to communicate effectively and develop critical thinking. Specific background: However, elementary school students often face challenges in organizing ideas, using proper grammar, and maintaining consistency in writing, which hinders their overall performance. Knowledge gap: Previous studies have highlighted the role of media in learning, yet there is limited evidence on the use of digital flipbook media to improve writing skills at the primary level. Aims: This study aims to examine the role of digital flipbook media in improving the writing skills of fourth-grade students at SD Negeri Wunut 1. Results: Using a pre-experimental one-group pretest-posttest design with 35 participants, the findings showed a significant improvement in students’ writing skills, indicated by the paired sample t-test (Sig. = 0.000 < 0.05). Novelty: The integration of interactive flipbook media provided not only engaging visuals but also strengthened students’ motivation and creativity in writing. Implications: These results suggest that digital flipbook media can serve as an effective alternative in elementary education, fostering both literacy development and digital literacy in the classroom. Highlights Digital flipbook significantly improves elementary students’ writing skills. Interactive media fosters motivation and creativity in literacy learning. Study supports digital-based innovation in primary school education. Keywords: Writing Skills; Digital Flipbook; Elementary Education; Literacy; Innovation